MENYOAL KUALITAS CALEG PEREMPUAN MENJELANG PEMILIHAN UMUM TAHUN 2024 DI ACEH - Aklima Aklima (Universitas Indo Global Mandiri, 2022)
ABSTRACT Women's political guarantees in the general elections have not met the 30% quota. This is in terms of the fulfillment of the selected women's quota. The dominance of political masculinity is still a record of problems in the representation of women in the political field. This study answers the problem of the quality of women's caleg ahead of the 2024 general election in Aceh using a qualitative approach to critical analysis through documentation and interviews. The results of the study showed that; The model of thinking Representation of substance that cultivates in the internal society so that women's social trust in women is not well established, the existence of political parties does not pay attention to women's political guarantees in realizing reserved seats. On the other hand, efforts to strengthen the quality of women's caleg ahead of the 2024 general elections can be carried out by optimizing affirmative action policies on the emphasis of reserved seats, optimizing the function of political parties to conduct political education for library candidates and strengthening political modalities in an effort to increase the percentage of women's representation in the legislature. Keywords : Women, Affirmative Action, General Election ABSTRAK Jaminan politik perempuan dalam pemilihan umum belum memenuhi kuota 30%. Hal ini ditinjau dari pemenuhan kuota perempuan yang terpilih. Dominasi maskulinitas politik masih menjadi catatan problematika dalam repersentasi perempuan dibidang politik. kajian ini menjawab persoalan kualitas caleg perempuan menjelang pemilihan umum tahun 2024 di Aceh dengan menggunakan pendekatan kualitatif analisis kritis melalui dokumentasi dan wawancara. Adapun hasil kajian menunjukkan bahwa; Model berpikir Representasi subtansi yang membudaya diinternal masyarakat sehingga social trust perempuan terhadap perempuan tidak terjalin dengan baik, keberadaan partai politik tidak memerhati jaminan politik perempuan dalam mewujudkan reserved seats. Dilain sisi upaya penguatan kualitas caleg perempuan menjelang pemilihan umum tahun 2024 dapat dilakukan dengan mengoptimalisasi kebijakan affirmative action pada penekanan reserved seats, optimalisasi fungsi partai politik untuk melakukan pendidikan politik bagi caleg perenpuan serta penguatan modalitas politik upaya meningkatkan persentase keterwakilan perempuan di legislatif. Kata Kunci : Perempuan, Affirmative Action, Pemilihan Umum